Zero self-explosion fireproof power generation glass

CN119638209BActive Publication Date: 2026-10-23BEIJING HAIYANG SHUNDA GLASS CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411928006.5
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-12-25
Publication Date
2026-10-23
Estimated Expiration
2044-12-25

AI Technical Summary

Technical Problem

[0005]本发明提出零自爆防火发电玻璃,解决了相关技术中防火发电玻璃耐温防火性能低的问题

Benefits of technology

本发明中,将防火功能与发电功能有机结合于发电玻璃之上,赋予发电玻璃可靠的防火能力,减少因火灾隐患、玻璃自爆导致的设备损坏与停机维修频次,保障光伏发电系统长期稳定运行,持续高效产出电能,提升光伏发电项目整体经济效益,本发明中,使用钛盐对三氧化二硼进行改性,制备得到隔热镀膜层通过在玻璃表面构建高效的隔热网络,有效阻止火焰热量穿透,提高防火发电玻璃的耐温防火性能。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application relates to the technical field of power generation glass, and discloses zero-self-explosion fireproof power generation glass which comprises, from bottom to top, a glass substrate and an absorption layer; the surface of the glass substrate further comprises a heat insulation coating layer, and the solid target material of the heat insulation coating layer is modified boron trioxide, which is obtained by modifying boron trioxide with a modifier; the modifier comprises a titanium salt. Through the technical scheme, the problem of low temperature resistance and fireproof performance of the fireproof power generation glass in the related art is solved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention relates to the field of power-generating glass technology, specifically to zero-explosion fireproof power-generating glass. Background Technology

[0002] With the increasing global demand for clean energy, photovoltaic power generation, as a sustainable and pollution-free energy acquisition method, is playing an increasingly important role in the energy sector. In photovoltaic power generation systems, photovoltaic glass, with its unique advantages, combines the functions of traditional architectural glass, such as light transmission and wind and rain protection, with the ability to efficiently convert solar energy into electricity. It is widely used in various building curtain walls, photovoltaic roofs, and other applications, achieving the dual benefits of building energy conservation and power generation revenue.

[0003] However, traditional photovoltaic power generation technology has significant drawbacks, one of which is the risk of fire. Once an electrical fire occurs in a photovoltaic power generation facility, it often spreads rapidly. Firstly, photovoltaic power generation systems involve numerous electrical lines, inverters, combiner boxes, and other equipment. Electrical problems such as short circuits, overloads, poor connections, and equipment malfunctions can easily ignite sparks, instantly igniting surrounding flammable materials, such as photovoltaic module encapsulation materials and protective coatings on mounting brackets. Furthermore, the large and interconnected nature of photovoltaic arrays provides a convenient "channel" for fire to spread, quickly covering large areas. Secondly, during a fire, numerous photovoltaic modules and associated electrical equipment release large amounts of toxic and harmful substances during combustion. Common examples include acidic gases such as hydrogen chloride and hydrogen fluoride, as well as organic pollutants such as polycyclic aromatic hydrocarbons and dioxins. These toxic substances permeating the air not only severely hinder on-site firefighting and rescue efforts, threatening the lives of rescue personnel, but also have long-term negative impacts on the surrounding environment, polluting soil, water sources, and air, and endangering the health of residents.

[0004] Among the many components of a photovoltaic power generation system, glass itself carries the risk of spontaneous breakage. Spontaneous breakage refers to the phenomenon where glass suddenly shatters and breaks without any significant external mechanical impact or other strong force. The causes are quite complex. Firstly, internal defects can cause this. During manufacturing, impurities such as iron filings in quartz sand or incompletely melted stones may be mixed into the glass sheet. These impurities have significantly different coefficients of thermal expansion from the glass matrix. When temperatures change, the inconsistent expansion or contraction causes stress concentration. When this stress exceeds the glass's tolerance limit, spontaneous breakage occurs. Secondly, defects in the tempering process can lead to uneven heating or improper cooling, resulting in uneven pre-stress distribution within the glass. During use, fluctuations in external environmental factors such as temperature and wind pressure can cause stress imbalance, prompting spontaneous breakage. Once photovoltaic glass spontaneously breaks, it not only directly results in the loss of its power generation function, but the scattered fragments can also damage surrounding equipment and building structures. More seriously, the broken glass surface is prone to dust and water accumulation in outdoor environments, potentially causing internal short circuits and becoming a contributing factor to electrical fires. Therefore, it is very necessary to develop a zero-self-explosion fireproof and power-generating glass. Summary of the Invention

[0005] This invention proposes a zero-self-explosion fireproof and power-generating glass, which solves the problem of low temperature resistance and fireproof performance of fireproof and power-generating glass in related technologies.

[0006] The technical solution of the present invention is as follows: The present invention proposes a zero-self-explosion fireproof and power-generating glass, which includes a glass substrate and an absorption layer from bottom to top; the surface of the glass substrate also includes a heat-insulating coating layer, wherein the solid target material of the heat-insulating coating layer is modified boron trioxide, wherein the modified boron trioxide is obtained by modifying boron trioxide with a modifier, wherein the modifier includes titanium salt.

[0007] As a further technical solution, the glass substrate is borosilicate glass.

[0008] As a further technical solution, the absorber layer is a cadmium telluride thin film.

[0009] As a further technical solution, the method for preparing the modified boron trioxide includes the following steps: modified boron trioxide is obtained by co-precipitation modification of boron trioxide and titanium salt.

[0010] As a further technical solution, the titanium salt includes one or both of titanium tetrachloride and titanium tetrafluoride.

[0011] As a further technical solution, the preparation method of the modified boron trioxide includes the following steps: S1. Boron trioxide is dispersed in solution I, stirred, filtered, and dried to obtain activated boron trioxide; S2. Disperse the activated boron trioxide in solution II to obtain a solution containing boron trioxide; S3. Disperse the titanium salt in solution III to obtain a solution containing the titanium salt; S4. Add the solution containing titanium salt to the solution containing boron trioxide, co-precipitate, filter, dry, and calcine to obtain modified boron trioxide.

[0012] As a further technical solution, the mass ratio of the titanium salt to the boron trioxide is 9~10:100.

[0013] As a further technical solution, in S1, solution I is a hydrochloric acid solution with a concentration of 0.1 mol / L, and the mass ratio of solution I to boron trioxide is 10:1.

[0014] As a further technical solution, the stirring time in S1 is 1~2 hours.

[0015] As a further technical solution, solution II in S2 is an octanol solution, and the mass ratio of solution II to boron trioxide is 10:1.

[0016] As a further technical solution, in S3, solution III is a hydrochloric acid solution, and the mass ratio of solution III to the titanium salt is 10:1.

[0017] As a further technical solution, the co-precipitation time in S4 is 10~20 min, the co-precipitation temperature is 60~80℃, and the pH is less than 1 during the co-precipitation process.

[0018] As a further technical solution, the calcination temperature in S4 is 400~450℃, and the calcination time is 30~40min.

[0019] As a further technical solution, the modifier also includes P,P-diphenyl hydrazine phosphate.

[0020] In this invention, based on titanium salt-modified boron trioxide, P,P-diphenyl hydrazine phosphate is used to perform secondary modification on titanium salt-modified boron trioxide, giving full play to the synergistic effect of the two modifications and forming multiple fire-resistant mechanisms. This effectively isolates oxygen, slows down heat penetration, and further improves the temperature resistance and fire resistance of fire-resistant power-generating glass.

[0021] As a further technical solution, the preparation method of the modified boron trioxide includes the following steps: dispersing P,P-diphenyl hydrazine phosphate in solution IV, adding boron trioxide modified with titanium salt, filtering and drying after modification to obtain modified boron trioxide.

[0022] As a further technical solution, the mass ratio of the P,P-diphenyl hydrazine phosphate to the titanium salt-modified boron trioxide is 6~7:50.

[0023] As a further technical solution, the solution IV is anhydrous ethanol, and the mass ratio of the solution IV to the titanium salt-modified boron trioxide is 10:1.

[0024] As a further technical solution, the modification temperature is 40°C and the modification time is 4 hours.

[0025] The present invention also proposes a method for preparing zero-self-explosion fireproof and power-generating glass, comprising the following steps: assembling a glass substrate and an absorption layer in sequence from bottom to top, and sputtering a solid target material on the surface of the glass substrate to form a heat-insulating coating layer, thereby obtaining zero-self-explosion fireproof and power-generating glass.

[0026] As a further technical solution, the vacuum level of the sputtering vacuum environment is 6×10⁻⁶. -4 Pa.

[0027] The working principle and beneficial effects of this invention are as follows: In this invention, fireproof and power generation functions are organically combined on the power generation glass, giving it reliable fire resistance, reducing equipment damage and downtime caused by fire hazards and glass spontaneous breakage, ensuring the long-term stable operation of the photovoltaic power generation system, continuously and efficiently producing electricity, and improving the overall economic benefits of the photovoltaic power generation project. In this invention, titanium salt is used to modify boron trioxide to prepare a heat-insulating coating layer. By constructing an efficient heat-insulating network on the glass surface, it effectively prevents the penetration of flame heat and improves the temperature resistance and fire resistance of the fireproof power generation glass. Detailed Implementation

[0028] The technical solutions of the present invention will be clearly and completely described below with reference to the embodiments of the present invention. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative effort are within the scope of protection of the present invention.

[0029] In the following examples and comparative examples: Glass substrate: High borosilicate fireproof glass, 8mm thick; Absorbing layer: Cadmium telluride thin film, 0.32 μm thick; Heat insulation coating layer: 120nm thick; Boron trioxide: average particle size is 100 nm.

[0030] Example 1 The preparation method of modified boron trioxide includes the following steps: S1. Weigh 10 parts of boron trioxide and add them to 100 parts of 0.1 mol / L hydrochloric acid solution. Stir for 1 hour, filter and dry to obtain activated boron trioxide. S2. Disperse the activated boron trioxide in 100 parts of n-octanol solution to obtain a solution containing boron trioxide; S3. Disperse 0.9 parts of titanium tetrachloride in 9 parts of hydrochloric acid solution to obtain a mixed solution containing titanium salt; S4. Add the solution containing titanium salt to the solution containing boron trioxide to obtain a modified solution. Control the pH of the modified solution to be less than 1, heat to 60℃, modify for 20 minutes, filter, dry, and calcine at 400℃ for 40 minutes to obtain modified boron trioxide, i.e., solid target material. The preparation method of zero-self-explosion fireproof and power-generating glass includes the following steps: assembling the glass substrate and the absorber layer sequentially from bottom to top, and then feeding them into a vacuum magnetron sputtering device to achieve a vacuum level of 6×10⁻⁶. -4 At Pa, a heat-insulating coating layer is formed by sputtering a solid target material onto the surface of the outer glass substrate, thus obtaining zero-explosion fireproof and power-generating glass, wherein the solid target material is modified boron trioxide obtained by the above preparation method.

[0031] Example 2 The preparation method of modified boron trioxide includes the following steps: S1. Weigh 10 parts of boron trioxide and add them to 100 parts of hydrochloric acid solution with a concentration of 0.1 mol / L. Stir for 1.5 h, filter and dry to obtain activated boron trioxide. S2. Disperse the activated boron trioxide in 100 parts of n-octanol solution to obtain a solution containing boron trioxide; S3. Disperse 0.9 parts of titanium tetrachloride in 9 parts of hydrochloric acid solution to obtain a mixed solution containing titanium salt; S4. Add the solution containing titanium salt to the solution containing boron trioxide to obtain a modified solution. Control the pH of the modified solution to be less than 1, heat to 70℃, modify for 15 min, filter and dry, and calcine at 420℃ for 35 min to obtain modified boron trioxide, i.e., solid target material. The preparation method of zero-self-explosion fireproof and power-generating glass includes the following steps: assembling the glass substrate and the absorber layer sequentially from bottom to top, and then feeding them into a vacuum magnetron sputtering device to achieve a vacuum level of 6×10⁻⁶. -4 At Pa, a heat-insulating coating layer is formed by sputtering a solid target material onto the surface of the outer glass substrate, thus obtaining zero-explosion fireproof and power-generating glass, wherein the solid target material is modified boron trioxide obtained by the above preparation method.

[0032] Example 3 The preparation method of modified boron trioxide includes the following steps: S1. Weigh 10 parts of boron trioxide and add them to 100 parts of hydrochloric acid solution with a concentration of 0.1 mol / L. Stir for 2 hours, filter and dry to obtain activated boron trioxide. S2. Disperse the activated boron trioxide in 100 parts of n-octanol solution to obtain a solution containing boron trioxide; S3. Disperse 0.9 parts of titanium tetrachloride in 9 parts of hydrochloric acid solution to obtain a mixed solution containing titanium salt; S4. Add the solution containing titanium salt to the solution containing boron trioxide to obtain a modified solution. Control the pH of the modified solution to be less than 1, heat to 80℃, modify for 10 min, filter, dry, and calcine at 450℃ for 30 min to obtain modified boron trioxide, i.e., solid target material. The preparation method of zero-self-explosion fireproof and power-generating glass includes the following steps: assembling the glass substrate and the absorber layer sequentially from bottom to top, and then feeding them into a vacuum magnetron sputtering device to achieve a vacuum level of 6×10⁻⁶. -4 At Pa, a heat-insulating coating layer is formed by sputtering a solid target material onto the surface of the outer glass substrate, thus obtaining zero-explosion fireproof and power-generating glass, wherein the solid target material is modified boron trioxide obtained by the above preparation method.

[0033] Example 4 The difference between Example 4 and Example 1 is that the amount of boron trioxide added is 1 part.

[0034] Example 5 The preparation method of modified boron trioxide includes the following steps: 1.2 parts of P,P-diphenyl hydrazine phosphate are dispersed in 100 parts of ethanol, 10 parts of boron trioxide are added, the mixture is heated to 40℃ and modified for 4 hours, and then filtered and dried to obtain modified boron trioxide.

[0035] The difference between Example 5 and Example 4 is that the solid target material is replaced with modified boron trioxide obtained by the above preparation method.

[0036] Example 6 The difference between Example 6 and Example 5 is that boron trioxide is replaced with an equal amount of modified boron trioxide prepared in Example 4.

[0037] Example 7 The difference between Example 7 and Example 6 is that the amount of P,P-diphenyl hydrazine added is 1.4 parts.

[0038] Comparative Example 1 Compared with Example 1, Comparative Example 1 differs in that a solid target is not sputtered onto the surface of the outer glass substrate to form a heat-insulating coating layer.

[0039] Comparative Example 2 The difference between Comparative Example 2 and Example 1 is that the solid target material is boron trioxide.

[0040] The zero-self-explosion fireproof and power-generating glass prepared in Examples 1-7 and Comparative Examples 1-2 was tested according to the following method: 1. Fire resistance integrity time: The fire resistance integrity time of the sample shall be tested in accordance with the test method specified in GB 15763.1-2009 "Safety glass for building - Part 1: Fire-resistant glass".

[0041] 2. Fire resistance limit: The fire resistance limit of the sample shall be tested in accordance with the test method specified in GB 15763.1-2009 "Safety glass for building - Part 1: Fire-resistant glass".

[0042] The test results are shown in the table below: Table 1 Performance test results of the zero-self-explosion fireproof and power-generating glass prepared in Examples 1-7 and Comparative Examples 1-2

[0043] Compared with Comparative Examples 1 and 2, Example 1 added modified boron trioxide obtained by titanium salt modification as a solid target material, and sputtered the solid target material on the surface of the outer glass substrate to form a heat-insulating coating layer. As a result, the fire resistance integrity and fire resistance limit of Example 1 were better than those of Comparative Examples 1 and 2, indicating that when modified boron trioxide obtained by titanium salt modification is added as a solid target material, the temperature resistance and fire resistance performance of fire-resistant power generation glass can be improved.

[0044] Compared with Examples 4 and 5, Examples 6 and 7 used titanium salt and P,P-diphenyl hydrazine phosphate to modify boron trioxide, and prepared modified boron trioxide as a solid target. The solid target was sputtered on the surface of the outer glass substrate to form a heat-insulating coating layer. As a result, the fire resistance integrity and fire resistance limit of Examples 6 and 7 were better than those of Examples 4 and 5, indicating that there is a synergistic effect between titanium salt and P,P-diphenyl hydrazine phosphate, which can further improve the temperature resistance and fire resistance performance of fireproof power generation glass.

[0045] The above are merely preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.

Claims

1. Zero-explosion fireproof and power-generating glass, characterized in that, From bottom to top, it includes a glass substrate and an absorption layer; the surface of the glass substrate also includes a heat-insulating coating layer, the solid target material of the heat-insulating coating layer is modified boron trioxide, the modified boron trioxide is obtained by modifying boron trioxide with a modifier, the modifier includes titanium salt; the modifier also includes P,P-diphenyl hydrazine phosphate; The method for preparing the modified boron trioxide includes the following steps: S1. Boron trioxide is dispersed in solution I, stirred, filtered, and dried to obtain activated boron trioxide; S2. Disperse the activated boron trioxide in solution II to obtain a solution containing boron trioxide; S3. Disperse the titanium salt in solution III to obtain a solution containing the titanium salt; S4. Add the solution containing titanium salt to the solution containing boron trioxide, co-precipitate, filter, dry and calcine to obtain boron trioxide modified with titanium salt. S5. Disperse P,P-diphenyl hydrazine phosphate in solution IV, add titanium salt modified boron trioxide, filter and dry after modification to obtain modified boron trioxide; Solution I is a 0.1 mol / L hydrochloric acid solution; Solution II is a n-octanol solution; Solution III is a hydrochloric acid solution; Solution IV is anhydrous ethanol.

2. The zero-explosion fireproof and power-generating glass according to claim 1, characterized in that, The glass substrate is borosilicate glass.

3. The zero-self-explosion fireproof and power-generating glass according to claim 1, characterized in that, The absorber layer is a cadmium telluride thin film.

4. The zero-self-explosion fireproof and power-generating glass according to claim 1, characterized in that, The titanium salt includes one or both of titanium tetrachloride and titanium tetrafluoride.

5. The zero-self-explosion fireproof and power-generating glass according to claim 1, characterized in that, The mass ratio of the titanium salt to the boron trioxide is 9~10:

100.

6. The zero-self-explosion fireproof and power-generating glass according to claim 1, characterized in that, The mass ratio of the P,P-diphenyl hydrazine phosphate to the titanium salt-modified boron trioxide is 6~7:50.

Citation Information

Patent Citations

  • Protective coatings for photovoltaic cells

    CN104205355A